Hubungan Antara National Institute of Health Stroke Score (NIHSS) dan Letak Lesi Pada Pasien Stroke Infark di Rumah Sakit Umum Daerah Dr. Soedarso Pontianak - Muhammad Alif Irsyam; Dyan Roshinta Laksmi Dewi; Muhammad In’am Ilmiawan (Riviera Publishing, 2022)
Introduction: Knowledge of the classic signs of early ischemia or the appearance of bleeding on computed tomography (CT) is required for satisfactory imaging studies. Computerized Tomography Scanning (CT-scan) without contrast of the head is the gold standard examination to determine the type of stroke pathology, location, and extension of the lesion and to exclude non-vascular lesions. The National Institute of Health Stroke Scale (NIHSS) is a systematic assessment tool that quantitatively measures stroke-associated neurologic deficits. The NIHSS is used as a clinical assessment tool to evaluate the severity of stroke patients, determine appropriate treatment, and predict patient outcomes. Objective: This study aims to determine the relationship between the National Institute of Health Stroke Score (NIHSS) and the location of lesions in patients with stroke infarcts at the Regional General Hospital dr. Soedarso Pontianak. Methods: This study applies an analytical research design with a cross-sectional design. Assessing the relationship between the National Institute of Health Stroke Score (NIHSS) and the location of the lesion in stroke infarct patients. Results: In this study, there was no effect of the NIHSS score on the location of the lesion in stroke infarct patients. The incidence of infarct stroke lesions occurred most often in the subcortical area, which occurred in 12 people. Stroke infarct patients experienced neurological deficits in the moderate category, which occurred in 10 people. Conclusion: There is no relationship between NIHSS and lesion location in stroke infarct patients at Dr. Hospital. Soedarso Pontianak. There is no relationship between NIHSS and lesion location in patients with stroke infarct at Dr. Hospital. Soedarso Pontianak.